Strategi Komunikasi Komunitas Kutai Literasi dan Budaya Etam untuk Membangun Kesadaran Masyarakat dalam Belajar Bahasa Isyarat - Astuti, Erlina Puji; Agustian, Jaka Farih (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to explain how the communication strategy of Kutai Literacy and Etam Culture Community to build public awareness in learning sign language and explain the supporting and inhibiting factors of Kutai Literacy and Etam Culture Community activities in building public awareness in learning sign language. Formulation of communication strategies with the stages of knowing the audience, compiling messages, determining methods and selecting the use of media using the Elaboration Likelihood Model. The research method used to understand this issue is descriptive qualitative aims to explain the phenomenon as deeply as possible. The results of this research conducted, researchers can draw conclusions on the communication strategy of the Kutai Literacy and Etam Culture Community to build public awareness in learning sign language. First, recognize the audience where Kaliya's audience is the general public and in social media are those who are friends with Kaliya's Instagram account. Second, composing the message in accordance with Kaliya's vision, mission and goal, which is to build inclusive education and help provide information accessibility to deaf or hard of hearing people. Third, determining the method in this case in delivering the message, Kutai Literacy and Etam Culture Community uses redundancy, persuasive, informative and educative. Fourth, the use of Kaliya media in delivering information directly through Car free day, socialization in the agency environment and Kaliya Goes to School and for indirect media is Instagram and Whatsapp. The Elaboration Lkelihood Model analysis of Kaliya on the Central line conveys a message that makes sense and is relevant to the Law and conveys the importance of learning sign language, on the peripheral line Kaliya tries to build a Positive Image and includes outstanding deaf figures in building public awareness. The supporting factors of Kaliya's activities are the support from government agencies and it is an independent community that is well known and the activities are rarely done. The inhibiting factor is the lack of human resources both from Kaliya members or volunteers and deaf friends who excel.